Complete mitochondrial genome sequences of a deep-sea holothurian species of the genus Scotoplanes (Elasipodida: Elpidiidae). Issue 1 (2nd January 2019) - Takano, Tsuyoshi; Ijichi, Minoru; Itoh, Hajime; Fukuda, Hideki; Yoshizawa, Susumu
Abstract: Two complete and one near-complete mitochondrial genomes (mitogenomes) were determined for a deep-sea holothurian species of the genus Scotoplanes (Elpidiidae). Each sequence contains two ribosomal RNA genes, 22 transfer RNA genes, and 13 protein-coding genes, as found in most previously determined holothurian mitogenomes. The protein-coding genes use ATG or ATA as the start codon, and TAA or TAG as the stop codon. Phylogenetic reconstruction using the maximum likelihood method confirmed the sister relationship between Scotoplanes sp. and another elpidiid holothurian Peniagone sp.; the three Scotoplanes sp. specimens were recovered as a monophyletic group.